2019
DOI: 10.18203/2320-6012.ijrms20190363
|View full text |Cite
|
Sign up to set email alerts
|

Study of histopathological spectrum of gallbladder in cholecystectomy specimens

Abstract: Background: Cholecystitis is one of the most common indications for abdominal surgery. Routine examination of gallbladder grossly and microscopically shows lot of interesting findings. This study aims to quantify the various outcomes of routine gallbladder examination following cholecystectomy procedure.Methods: All clinical details and data from case sheet and patient history are collected and analysed for all the patients who underwent cholecystectomy surgery in the Department of General Surgery, Govt. Omand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…In the present study of 161 cases, 49 cases (30.43%) were in third decade which is consistent with the study conducted by Narendra et al 7 Females were found to be predominantly affected (65.22%) compared to males (34.78%) which is similar to the studies conducted by Beena D et al, Srinivasan G et al, Sharma I et al [8][9][10] Table 3 shows comparison of age group distribution. Out of 161 cases, 160 cases (99.38%) were complaining of pain in epigastrium followed by nausea/vomiting (6.83%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study of 161 cases, 49 cases (30.43%) were in third decade which is consistent with the study conducted by Narendra et al 7 Females were found to be predominantly affected (65.22%) compared to males (34.78%) which is similar to the studies conducted by Beena D et al, Srinivasan G et al, Sharma I et al [8][9][10] Table 3 shows comparison of age group distribution. Out of 161 cases, 160 cases (99.38%) were complaining of pain in epigastrium followed by nausea/vomiting (6.83%).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, majority (93 cases, 57.76%) of the cases were diagnosed as chronic calculus cholecystitis which had presented as pain in abdomen in the right hypochondrium followed by chronic acalculus cholecystitis (36 cases, 22.36%) which is similar to study conducted by Srinivasan et al, and Sharma et al, but differs from studies conducted by Goyal et al, and Arathi et al, in which chronic acalculus cholecystitis was the histopathological diagnosis in majority of the cases. 9,10,17,18 In the present study, remaining cases are of Acute on chronic Cholecystitis (6.21%), Acute on chronic cholecystitis with cholelithiasis (4.96%), Acute on chronic cholecystitis with perforation peritonitis, Biliary Atresia, Chronic cholecystitis with choledochal cyst, Follicular Cholecystitis and Xanthogranulomatous cholecystitis (1.24% each) ( Figure 2). One case (0.62%) of Acute suppurative cholecystitis with perforation peritonitis was also found.…”
Section: A B a Bmentioning
confidence: 51%
“…Several other studies also reported chronic cholecystitis as the most common lesion in gall bladder specimens. [3][4][5][6] Surprisingly Uysal et al 11 and Siddiqui et al 12 observed 95% and 92% of cholecystectomy specimens diagnosed with chronic cholecystitis respectively.…”
Section: Discussionmentioning
confidence: 99%
“…4 Cholecystectomy is the most commonly performed surgical procedure for gall bladder diseases and the majority of the cholecystectomies are done for cholelithiasis affecting 10% to 20% of adult population in developed countries. 5 More than 95% of biliary tract disease is attributed to cholelithiasis and its prevalence increases with age from 21 to 80 years and higher in females than males whereas gallbladder cancer is the most common malignancy of the extra hepatic biliary tract. 6,7 Surgical removal of gall bladder is common and the cholecystectomized gall bladder specimens are one of the frequently received specimens in the department of Pathology.…”
Section: Introductionmentioning
confidence: 99%
“…A valve, which opens only when food is present in the intestine, allows bile to flow from the common bile duct into the duodenum (upper intestine) where it functions in the process of fat digestion. 1 Sometimes the substances contained in bile crystallize in the gall bladder, forming gallstones. These small, hard concretions are more common in persons over 40, especially in women and obese individuals.…”
Section: Introductionmentioning
confidence: 99%